Kajian Kajian Aspek Visibility dan Legibility Signage pada Royal Plaza Mall Surabaya - Syifa Kamila Syifa (Jurnal Mahasiswa Departemen Arsitektur, 2023)
Signage is known as directions, road signs, location instructions, or information instructions so that it can communicate between the architecture and its users on the exterior and interior landscape of the building. The mall is a public facility with a complex type of space; mall visitors are regular old visitors and new visitors who come to the mall for the first time. So it takes markers and directions so that visitors feel comfortable. The purpose of this study was to determine the visibility and legibility aspects of the signage design at Royal Plaza Mall Surabaya which includes typography, color, layout, and signage installation position. The method used is a qualitative descriptive analysis method by explaining the condition of the signage at the Royal Plaza Mall Surabaya in detail according to the facts on the ground. Next, examine the signs based on existing theories in the form of a literature review. The findings from this study are that in general, the signage design of Royal Plaza Mall Surabaya in terms of visibility and legibility with the observation units for typography, color, layout, and signage installation positions are in accordance with the standards in theory. However, when signage is identified in more detail according to aspects of each research unit, some signage still has deficiencies in legibility aspects such as letter spacing, the vertical spacing between typography, and the use of colors that are not quite right on identification signs.